The use of probability models for simplified estimates of required reserves reliability control - Yu. V. Feshkin (Научный вестник МГТУ ГА)
The article discusses the use of a probabilistic model for simplified assessments required reserves reliability control (crack detection probability). Ratios and charts for estimating reliability coefficients of the probability of detection of a fatigue crack are given. The use of safety factors equal to 2 ... 3 possible with a high quality of diagnosis (probability of detecting fatigue crack greater than 0.95) is shown.